Identifikasi Kesalahan Siswa Dalam Menyelesaikan Soal Matematika Berdasarkan Metode Analisis Kesalahan Newman - Safitri, Darni (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2017)
Students attempted to implement procedures Newman while working on math problems. However, because less familiar, often the step that is not done, namely in step to understand the problem and transformation. For these types of mistakes made by the students while work on the problems, there are no students who perform this type of read errors. The new fault of the student in the time to understand the problem. This type of error is the error made in understanding the problem. The reason is the lack of students' ability to create illustra-tions, less careful in drawing so illustrations drawn not in accordance with the intended and do not ignore because mera-sa unnecessary. Subsequent Error type students is an error in processing capability.